2012
DOI: 10.1099/jmm.0.037895-0
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility profiles of Candida isolates from a prospective survey of invasive fungal infections in Italian intensive care units

Abstract: The antifungal susceptibility pattern of 302 Candida isolates collected during an Italian survey on invasive fungal infections in an intensive care setting was investigated. The results were correlated with some epidemiological data and compared with the antifungal profiles obtained in a previous survey. No resistance to echinocandins was detected. The overall resistance levels to fluconazole, posaconazole and voriconazole were 12.6, 6.0 and 7.1 %, respectively. Candida tropicalis and Candida parapsilosis acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
4
7
1
1
Order By: Relevance
“…Similar results were reported by other researchers (14,20,(24)(25)(26) (26). They also reported that all strains of C. parapsilosis were susceptible to caspofungin, while 1% and 1.2% of C. parapsilosis isolates from Latin America and North America, respectively, were resistant to anidulafungin (26).…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were reported by other researchers (14,20,(24)(25)(26) (26). They also reported that all strains of C. parapsilosis were susceptible to caspofungin, while 1% and 1.2% of C. parapsilosis isolates from Latin America and North America, respectively, were resistant to anidulafungin (26).…”
Section: Discussionsupporting
confidence: 88%
“…There have been, however, increases in HI caused by non-C. albicans Candida (NCAC) species such as C. tropicalis, C. glabrata, C. parapsilosis, and C. krusei [6][7][8] . The occurrence of infections caused by these yeasts is relevant to HI vigilance because these micro-organisms have varying virulence attributes and profi les of antifungal drug sensitivity, including recent reports of resistance to the principal antifungal drugs currently administered in hospitals 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Candida species can cause various clinical manifestations ranging from superficial to systemic candidiasis in either immunocompetent or immunocompromised hosts (Garcia-Hermoso et al, 2007;Odds et al, 2007;Pfaller & Diekema 2007;Fesharaki et al, 2013). Infections due to C. albicans are an important cause of morbidity and mortality among hospitalized patients who have been admitted to intensive care units (ICUs) and in oncology wards worldwide (Bougnoux et al, 2006(Bougnoux et al, , 2008Horn et al, 2009;Tortorano et al, 2012;Sardi et al, 2013). Burn patients are especially susceptible to Candida infections because they have most of the risk factors for hospital-acquired fungal infections, i.e.…”
Section: Introductionmentioning
confidence: 99%